Extracorporeal Organ Support in Cardiorenal Syndrome - María Jimena (Journal of Cardiology and Cardiovascular Medicine, 2025)
Introduction: The term “Cardiorenal Syndrome” [CRS] is widely used to make reference to the vast array of interrelated, bidirectional interactions between heart-kidney derangements. Objective: In the present manuscript, a brief description of CRS-related operational definitions and physiopathological mechanisms will be made, in order to better describe the therapeutic benefits of the use of ECOS in CRS patients, including achieving euvolemic state via ultrafiltration, inflammatory pathways regulation via hemadsorption and ECMO-provided hemodynamic support. Discussion: Even when there is a high heterogenicity among cardiorenal syndrome clinical scenarios, common physiopathological pathways have been described, including neurohormonal adaptations, and hemodynamic changes, right ventricle dysfunction, oxidative stress and proinflammatory pathways. Therapeutic benefits of the use of ECOS in CRS patients, include achieving euvolemic state via ultrafiltration, regulation of inflammatory pathways via hemoadsorption and ECMO-provided hemodynamic support. Conclusion: Extracorporeal organ support represents a valuable therapeutic strategy for patients with cardiorenal syndrome. In the years to come, the potential of ECOS as an inflection point in the natural history of disease to prevent the development of organ failure, prevent single organ failure becoming a multiorgan failure, prevent chronic organ failure development and achieving full recovery will be among the most important subjects within the research agenda.